Promoting a Culturally Safe Evaluation of an On-the-Land Wellness Program in the Inuvialuit Settlement Region - Ollier, Mary; Giles, Audrey R.; Etter, Meghan; Ruttan, Jimmy; Elanik, Nellie; Goose, Ruth; Ipana, Esther (ARCTIC, 2020)
In 2017, the Inuvialuit Regional Corporation partnered with a diverse research advisory team to understand howProject Jewel, a land-based program in the Inuvialuit Settlement Region, could be evaluated in a way that promotes cultural safety (i.e., in a way that addresses the social, historical, and economic contexts that shape participants’ experiences). We used community-based research methodology to approach the study, through which semi-structured interviews, sharing circles, and photovoice were identified by the community advisory board and research advisory team as appropriate research methods for this project. After piloting and evaluating these methods, we then used thematic analysis to analyze the data, which included images and transcripts, to identify the components of a culturally safe evaluation: centring the land, building relationships, working with words and pictures, and promoting benefit over harms through program aftercare. Our community-based research and findings provide a template of a meaningful evaluation framework that other on-the-land programs can use ifcontextualized within local cultural practices and values. En 2017, l’Inuvialuit Regional Corporation s’est associée à une équipe de recherche consultative diversifiée pourtâcher de comprendre comment le projet Jewel, programme terrestre mené à bien dans la région désignée des Inuvialuit, pourrait être évalué de manière à favoriser la sécurité ou sécurisation culturelle (c’est-à-dire de manière à tenir compte des contextes social, historique et économique ayant façonné les expériences des participants). Nous nous sommes servis d’une méthodologie de recherche communautaire pour aborder l’étude. Grâce à cette méthodologie, le conseil consultatif communautaire et l’équipe de recherche consultative ont déterminé que des entrevues semi-structurées, des cercles de partage et des recherches par amorce photo étaient des méthodes de recherche convenant bien à ce projet. Après avoir mis ces méthodes à l’essai et les avoir évaluées, nous avons ...